Application of 19F NMR Spectroscopy for Content Determination of Fluorinated Pharmaceuticals - Alex O. Okaru; Tobias S. Brunner; Svenja M. Ackermann; Thomas Kuballa; Stephan G. Walch; Matthias Kohl-Himmelseher; Dirk W. Lachenmeier (Journal of Analytical Methods in Chemistry)
A simple, rapid, and selective quantitative nuclear magnetic resonance spectroscopic method was evaluated for the determination of the content of fluorinated pharmaceuticals. 19F NMR spectra were either obtained in dimethylsulfoxide-d6 or aqueous buffer, using trifluoroacetic acid as internal standard. Quantification of 13 fluorine-containing pharmaceuticals spanning various pharmacological classes was accomplished using the proposed method. The method was found to be fit for purpose (interday precision 1.2% relative standard deviation) and may thus be applied for routine analysis and quality control of fluorine-containing pharmaceuticals due to its simplicity, nondestructive sample measurement, reliability, and high specificity. Therefore, 19F NMR may serve as a suitable analytical tool for the identification and selective determination of fluorinated pharmaceuticals used as reference materials and bulk samples.